2022
DOI: 10.3390/ijerph19053097
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Amnestic and Non-Amnestic Mild Cognitive Impairment and Its Association with Different Lifestyle Factors in a South Italian Elderly Population

Abstract: Mild Cognitive Impairment (MCI) is a transition stage between normal aging and dementia and can be useful to monitor the cognitive status of people at risk of dementias. Our aims were to investigate the prevalence of amnestic and non-amnestic MCI in a South Italian elderly population, and to identify socio-demographic, clinical and lifestyle factors associated with MCI. A cross-sectional retrospective population study on 839 community-dwelling participants over 60 years of age was carried out. Elderly people w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Thus, our population can be regarded as representative of a typical HD population. In addition, we observed a higher prevalence of MCI and malnutrition compared to an age-matched population without CKD [ 48 , 49 ]. This identifies the role of CKD in increasing the risk of nutritional and cognitive alterations [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our population can be regarded as representative of a typical HD population. In addition, we observed a higher prevalence of MCI and malnutrition compared to an age-matched population without CKD [ 48 , 49 ]. This identifies the role of CKD in increasing the risk of nutritional and cognitive alterations [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no studies have focused on the association between lifestyle and genetic risk ( APOE and MTHFR ) in the development of MCI, and most have focused on single lifestyle factors or the APOE gene instead of combined factors . A cross-sectional study of Chinese adults aged 80 years or older showed that healthy lifestyle was associated with better cognitive function in older adults, regardless of APOE genotype .…”
Section: Discussionmentioning
confidence: 99%
“…Risk of MCI with lifestyle factors and genetic risks was further analyzed in sensitivity analyses using the combinations of unweighted lifestyle categories and weighted genetic risks, weighted lifestyle categories and unweighted genetic risks, and unweighted lifestyle categories and unweighted genetic risks. Additionally, we added BMI to lifestyle to recalculate this association, considering that some studies counted BMI as a lifestyle factor . We considered a BMI of 18.5 to less than 24 as a healthy lifestyle factor according to the revised Asia-Pacific BMI criteria by the World Health Organization and the National Health Commission of the People’s Republic of China .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amnestic MCI is a subtype of MCI manifesting as a decline in various types of memory (Leyhe et al, 2009 ; Costa et al, 2011 ; Tuena et al, 2021 ). The prevalence of amnestic MCI in people aged ≥60 was 7.4% in South Italy and 17.1% in China (Li et al, 2020 ; Caffo et al, 2022 ). Older patients with amnestic MCI are more likely to progress to Alzheimer’s dementia than those with non-amnestic MCI (Jungwirth et al, 2012 ).…”
Section: Amelioration Of the Clinical Symptoms Of MCI Through Tai Chi...mentioning
confidence: 99%